Role of GuaB, the inosine-5′-monophosphate dehydrogenase of uropathogenic Escherichia coli pathogenicity: a key factor for bladder infection - Mizuki Shimokawa; Ayako Takita; Kazutomo Suzue; Ayuko Kimura; Himari Tabo; Yumika Sato; Yuya Yanagita; Takuya Sadahira; Haruyoshi Tomita; Hidetada Hirakawa (Microbiology Spectrum)
ABSTRACT Uropathogenic Escherichia coli (UPEC) is the primary causative agent of urinary tract infections (UTIs). This bacterium infects the bladder through the urinary tract, and some bacteria ascend to the kidneys, leading to more severe conditions such as pyelonephritis and sepsis. The infection of the bladder by UPEC is a critical initial step in the development of UTIs. Once inside the bladder, UPEC forms microcolonies both within and outside bladder epithelial cells, allowing it to persist in the bladder by resisting urine flow, innate immunity, and antimicrobials. In this study, to look for novel factors of UPEC that contribute to bladder infection and persistence, we analyzed proteins expressed at significant levels by UPEC in the bladder using a UTI mouse model. Mass spectrometry detected over 30 candidate proteins, including those already reported to play important roles in bladder infection, such as OmpA, components of the iron acquisition system, and the Tol/Pal system. Among them, GuaB (inosine-5′-monophosphate dehydrogenase) emerged as a key factor for bladder infection. The GuaB mutant showed impaired growth in urine-mimicking conditions and reduced infection efficiency, attributed to decreased GMP production. GuaB expression was upregulated in urine-like conditions, influenced by urea. This highlights GuaB’s role in UPEC pathogenicity. These findings suggest GuaB as a potential target for new therapeutic strategies against UPEC-related UTIs, especially amid growing antimicrobial resistance.IMPORTANCEUropathogenic Escherichia coli (UPEC) is the most common cause of urinary tract infections (UTIs). UTI caused by UPEC is often recurrent, and repeated use of antimicrobial agents is feared to lead to the spread of drug-resistant strains. In fact, quinolone-resistant and extended spectrum β-lactamase-producing strains have been rapidly increasing since 2000. Therefore, improvement of current treatment methods, including new therapeutic agents against UPEC, is desired. In this study, we analyzed proteins significantly expressed in the bladder of UTI mice by proteomic analysis in order to identify new factors contributing to UPEC infection of the bladder. Among them, we found GuaB (inosine-5′-monophosphate dehydrogenase), which is important for bladder infection. Furthermore, we characterized the role of GuaB in bladder infection and the mechanism by which GuaB induces its expression in urine. Our findings will contribute not only to further understanding of UPEC pathogenesis but also to the development of new antimicrobial strategies.